The enterprise value in assessing the methodological approach (Journal of Economic Research & Business Administration, 2016)
The task of business valuation occurs at different stages of development of the enterprise, and never loses its relevance. Therefore enterprise value evaluation techniques, frequently used in practice. The income approach is one of the most important concepts is the income capitalization. It is measured in terms of potential profit opportunities in the value of the object, methods and collections. The acquisition of real property appraiser using the income approach measures the current value of future income. Stream of income during the period of ownership and recapitalization ratio using the current value of the profit from the sale of the property are capitalized. The history of mankind shows that people always aimed to live in the best natural environment – in the fertile lands, have convenient harbors in auspicious climate, the presence of water and fuel resources, in areas where the bearing capacity of soil, the depth and other natural characteristics auspicious for construction. Staying in such places, people built houses, public buildings, religious buildings, industrial and farm buildings, public facilities, combined their roads auspicious territory settlements, adapted them for life. Economic development, business activity, the relevant laws determined the style and standard of living and behavior.
Keywords: " business valuation; real estate prices; the estimated value; сapitalization rate. "